-96=-6g+2g

Simple and best practice solution for -96=-6g+2g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -96=-6g+2g equation:


Simplifying
-96 = -6g + 2g

Combine like terms: -6g + 2g = -4g
-96 = -4g

Solving
-96 = -4g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '4g' to each side of the equation.
-96 + 4g = -4g + 4g

Combine like terms: -4g + 4g = 0
-96 + 4g = 0

Add '96' to each side of the equation.
-96 + 96 + 4g = 0 + 96

Combine like terms: -96 + 96 = 0
0 + 4g = 0 + 96
4g = 0 + 96

Combine like terms: 0 + 96 = 96
4g = 96

Divide each side by '4'.
g = 24

Simplifying
g = 24

See similar equations:

| -2*4-3y=-7 | | 2x-24x=-72 | | -8h+10=-9h+18 | | p^2-2p=-1 | | -9f-6f=24 | | -2*2-3y=-7 | | X^5=65 | | 6=v+5v | | 48=5y-12 | | -3-4z=-15 | | 9x-6=12x-3x | | 3(-2x-1)=2x+5 | | 4(1+5g)= | | 4x+12+2x= | | 4(1+5g)=Submit | | (5x-2)+(2x+8)+90=180 | | 11j-6j+4j=18 | | 7(4p+1)= | | 2x^5=130 | | 2(1+3n)= | | 5(2+5h)= | | 4x-5=-x-5 | | 135x=4 | | 8m-29=59 | | 4x+12+3x= | | X=y-35 | | 3q+5q=48 | | 3(x+7)+6x=9x-21 | | 4x+8x^2=3 | | 15x=2.50 | | -28=3+8(n+6) | | 4(-2x+3)=-6y |

Equations solver categories